Analisis komoditas unggulan sektor pertanian - Achmad Faqih (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2021)
One of the steps to inventory/identify regional economic potential is to identify potential, mainstay and superior products of the region in each sub-sector. This research was conducted to find out what commodities are the leading sectors of agriculture in Indramayu Regency as well as changes and shifts in the basic commodities of the agricultural sector in Indramayu Regency. This study uses quantitative descriptive research methods. The research sample consisted of 31 districts. The object of this research is data on the development of agricultural commodities in the Department of Agriculture, Indramayu Regency. The data used in this study is secondary data, namely data on agricultural sector commodity production in Indramayu Regency during the 2015-2019 period. The results showed that: the main commodities of Indramayu Regency in its sub-sector were food crops, namely superior rice in 28 sub-districts, superior green beans in nine districts, peanuts, cassava and sweet potatoes. In four sub-districts, maize and soybeans are superior in three sub-districts, besides that the growth of rice, mango, jackfruit and papaya commodities in Indramayu Regency is included in the advanced or progressive group because of its positive value.